Association Between Meteorological Factors and the Rupture of Intracranial Aneurysms. Issue 17 (3rd September 2019) - Li, MeiHua; Hu, Si; Yu, NianZu; Zhang, Ying; Luo, Muyun
Abstract : Background: Both meteorological factors and morphological factors are important factors to predict intracranial aneurysm rupture. This study investigated the relationship between meteorological factors and aneurysmal subarachnoid hemorrhage (aSAH). Additionally, the morphological differences between ruptured and unruptured aneurysms under these high‐risk meteorological conditions were assessed. Methods and Results: The records of 1751 patients with aSAH with 2124 intracranial aneurysms were retrospectively analyzed. Spearman rank correlation analysis was used to assess the risks of incident aSAH on the basis of daily meteorological data. Morphological parameters were analyzed using 1‐way ANOVA tests, and significant parameters ( P <0.05) were further examined using a multivariable logistic regression analysis. Daily aSAH incidence had significant negative correlations with daily mean, maximum, and minimum temperature ( P <0.001) and a significant positive correlation with daily mean atmospheric pressure ( P <0.001). Additionally, 58 patients with multiple aneurysms were assessed to determine morphological differences. There were significant differences in the mean values for aneurysm size, neck width, length, height, width, parent artery diameter, shape of the aneurysm, aspect ratio, size ratio, and bottleneck factor ( P <0.05). The multivariable logistic regression analysis showed that aspect ratio (β=1.277, odds ratio=3.585, 95% CI, 1.588–8.090; P =0.002) was an independent risk factor for aneurysm rupture. Receiver operating characteristic curve analysis indicated that the ruptured aneurysm threshold of size was 3.45 mm and aspect ratio was 1.05. Conclusions: Lower daily mean, maximum, and minimum temperatures and a higher daily mean atmospheric pressure were associated with an increased rate of aSAH. Additionally, under these meteorological conditions, the aneurysm size and aspect ratio thresholds for predicting rupture of an aneurysm may be lower.